Maintaining quality of Lisbon lemon (Citrus limon) in cold storage using natural elicitors - Nasim Rastgoo; Somayeh Rastegar; Abbas Rohani (Journal of Horticulture and Postharvest Research, 2024)
Purpose: Lemon (Citrus limon) is a highly important citrus species worldwide. However, its semi-tropical nature makes it susceptible to chilling, extensive research on postharvest treatments to preserve its quality under low temperatures. Research Method: The treatments included 500 μM melatonin (M), 50 μM methyl jasmonate (J), and 5 mM gamma-aminobutyric acid (GABA). Lemons stored at 3 ± 1°C and a relative humidity of 85-95% for 100 days plus 5-day shelf life. Findings: The results revealed that most of the experimental treatments, except for the combination of GABA + J and GABA + J + M, significantly reduced fruit weight loss. Notably, the melatonin treatment showed a 22.7% lower weight loss compared to the control fruits. Furthermore, the melatonin treatment exhibited the highest fruit firmness (49 N), while the control treatment had the lowest (36.3 N). Regarding the quality parameters, individual treatments, and the GABA + M treatment resulted in significantly higher total soluble solids (TSS) and a lower TSS/TA compared to the control at the end of the storage period. Except for the M + GABA and M + J treatments, all other treatments showed higher ascorbic acid content compared to the control. Additionally, the melatonin treatment showed significant differences in various color indices compared to the control. Research limitations: There was no limitation. Originality/Value: Overall, fruits treated with M, J, GABA, and GABA + M demonstrated higher marketability compared to the control and other treatments. Consequently, it is recommended to utilize these treatments individually rather than in combination to maintain the quality of lemon fruits.